PROFITABILITY, FIRM AGE, AND LEVERAGE: ESTIMATION OF PANEL DATA MODELS IN THE EMERGING INDONESIAN MARKET - Rizka Hadya (Jurnal Apresiasi Ekonomi, 2019)
The purpose of this research is to test the influence of profitability and age, to the leverage. The type of data used was quantitative data taken from the company's annual financial statements and the company’s annual report summary. The population is all companies which are listed in Indonesia Stock Exchange in the last periods 2017. The sample collection technique has been carried out by using purposive sampling, 96 companies have been selected as samples. The data of the financial statement of the companies has been obtained from the official website of IDX. We tested the relationships between the profitability and firm age to leverage with the statistical method used is regression analysis in panel data. The result of the research shows, with partial test profitability and firm age, has a negative significant influence to the leverage. And then, estimation results show the r-square value of 91,76% which means the profitability and age of the company have the ability to explain leverage of 91,76% and while remaining 8,24% is explained by other variables which are not studied. Keywords: leverage, profitability, firm age